THE IMPACT OF BRIKS FROM ECONOMIC, LEGAL AND POLITICAL ASPECT IN THE INTERNATIONAL COMMUNITY - Mirjana Matovska; Jasmina Trajkoska; Zorica Siljanovska (European Scientific Journal, ESJ, 2014)
The influence of the BRICS countries is continuously increasing. Economic growth of these countries allows them stronger international influence. If you take into account that even half of the world population lives in these countries, shows the power that this block carries. Although it is a relatively new group, attempts to consolidate its activities on economical, legal and political sphere are continuous. Globalization and the current economic situation, enable BRICS countries to move current economic superpowers and ensure its dominance in the world. BRICS will change the geopolitical balance? Will these countries, which are in continuous growth in recent years, be able to be leaders of modern times dictation’s of economical and political future trends? Economic power always goes hand in hand with increased political influence. Are required internal political reforms in the BRICS countries to maintain continuity in economic development?